2014
DOI: 10.1515/hf-2014-0030
|View full text |Cite
|
Sign up to set email alerts
|

Novel hydrophobization of wood by epoxidized linseed oil. Part 2. Characterization by FTIR spectroscopy and SEM, and determination of mechanical properties and field test performance

Abstract: Scots pine samples were impregnated with epoxidized linseed oil (ELO) by means of a two-step process, and the effect of treatments has been studied concerning the Fourier transform infrared (FTIR) spectra, mechanical properties, moisture uptake, and field test performance. FTIR analysis of ELO-treated samples revealed that part of the ELO epoxy reactive group was chemically bound to the hydroxyl groups of wood. ELO-treated samples have improved dimensional stability, while the mechanical properties were slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…AA was added to the ELO emulsion and ELO/CW emulsion formulations, and thus the spectral results were more complicated than those of the CW emulsion-treated wood. The bands at 1375 and 1740 cm −1 correspond with a methoxy group and C=O, respectively [19,45]. The enhancement of band intensities at 1740 cm −1 is attributed to an intrinsic triglyceride structure and the grafting of acetic acid onto epoxidized linseed oil [19].…”
Section: Chemical Structure Analysis Using Ftir Spectroscopymentioning
confidence: 95%
See 3 more Smart Citations
“…AA was added to the ELO emulsion and ELO/CW emulsion formulations, and thus the spectral results were more complicated than those of the CW emulsion-treated wood. The bands at 1375 and 1740 cm −1 correspond with a methoxy group and C=O, respectively [19,45]. The enhancement of band intensities at 1740 cm −1 is attributed to an intrinsic triglyceride structure and the grafting of acetic acid onto epoxidized linseed oil [19].…”
Section: Chemical Structure Analysis Using Ftir Spectroscopymentioning
confidence: 95%
“…The spectra of LO and ELO were detected by adding a drop of the oil sample on the infrared probe to investigate the chemical group. The spectra were normalized to the peak at 1460 cm −1 (CH 2 scissors deformation vibration) [19].…”
Section: Synthesis Of Epoxidized Linseed Oil (Elo)mentioning
confidence: 99%
See 2 more Smart Citations
“…A positive result was also achieved when ELO was used alongside creosote present at 30 kg/m 3 ; the loss of MOE after 42 months of exposure was only 8%. Scots pine samples impregnated with ELO showed the effect of the treatment on the induced chemical changes (Jebrane et al 2015b). FTIR analysis of ELO-treated samples revealed that part of the ELO epoxy reactive group was chemically bound to the wood hydroxyl groups, i.e.…”
Section: Inground Testmentioning
confidence: 99%